2019
DOI: 10.1088/1757-899x/692/1/012022
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Life Calculation of High-Power Disc Brake under Thermal-Mechanical Coupling

Abstract: The fatigue failure mode of the brake disc is the initiation and expansion of the fatigue crack on the surface of the brake disc until the brake disc brakes. Therefore, considering the fatigue failure mode of the brake disc, the fatigue life of the brake disc is calculated. Firstly, the thermo-mechanical coupling model of the brake disc and pad is established by Abaqus software, so that temperature and stress of the brake disc could be obtained. Then, the surface crack initiation life of the brake disc is calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…27 This result also indicates that the rotation track of the frictional heat source should receive more attention than other parts since the high-temperature gradients are a potential cause of thermal cracking and wear. 29…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…27 This result also indicates that the rotation track of the frictional heat source should receive more attention than other parts since the high-temperature gradients are a potential cause of thermal cracking and wear. 29…”
Section: Resultsmentioning
confidence: 99%
“…27 This result also indicates that the rotation track of the frictional heat source should receive more attention than other parts since the high-temperature gradients are a potential cause of thermal cracking and wear. 29 Based on Figure 13(a)-(d), as the simulation time increased, the temperature of the traveler rose. Also, the high-temperature region was concentrated at the foot portion of the traveler, which was in direct contact with the ring and received the fixed frictional heat flux.…”
Section: Model Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the fatigue studies conducted for automotive brakes, Zhang’s paper [ 11 ] uses a combination of ABAQUS, Fe-safe, and nCode software to obtain the location, life, and crack length of fatigue crack initiation on the brake subjected to thermomechanical stress and, thus, obtains a fatigue life prediction method of the brake disc. Choi and Lee [ 12 ] found that the circumferential stress produced during rotation led to the failure of the solid automobile brake disc.…”
Section: Introductionmentioning
confidence: 99%
“…The finite element model as a powerful simulation tool was widely used to analyze temperature distributions for high-speed rotating friction systems. 4,19,20 In this study, the heat transfer model of the traveler and the ring was developed to reveal its temperature field through the external heat source method. 17 The ring temperature under four variables (traveler weight, yarn count, twist level and spindle speed) was obtained experimentally and simulated based on the experimental plan generated by the response surface methodology 21,22 to verify the correctness of the heat transfer model.…”
mentioning
confidence: 99%